2019
DOI: 10.1101/2019.12.13.870220
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

3D Bioprinting of Architected Hydrogels from Entangled Microstrands

Abstract: 31Hydrogels are an excellent biomimetic of the extracellular matrix and have found great 32 use in tissue engineering. Nanoporous monolithic hydrogels have limited mass transport, 33 restricting diffusion of key biomolecules. Structured microbead-hydrogels overcome some 34 of these limitations, but suffer from lack of controlled anisotropy. Here we introduce a 35 novel method for producing architected hydrogels based on entanglement of microstrands. 36 The microstrands are mouldable and form a porous str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
(38 reference statements)
1
15
0
Order By: Relevance
“…[311][312] Kessel et al showed that elongated gel microstands were also applicable to extrusion bioprinting (Figure 19). 313 High-aspect ratio HA-MA microstrands entangled, producing a printed construct with greater stability compared to spherical granular gels. The microstrand constructs did not need to be secondarily crosslinked and the properties of the printed bioink could be adjusted by the time of exposure of the bulk gel to UV light.…”
Section: Figure 19 Common Strategies To Achieve Good Extrusion Printabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…[311][312] Kessel et al showed that elongated gel microstands were also applicable to extrusion bioprinting (Figure 19). 313 High-aspect ratio HA-MA microstrands entangled, producing a printed construct with greater stability compared to spherical granular gels. The microstrand constructs did not need to be secondarily crosslinked and the properties of the printed bioink could be adjusted by the time of exposure of the bulk gel to UV light.…”
Section: Figure 19 Common Strategies To Achieve Good Extrusion Printabilitymentioning
confidence: 99%
“…An added advantage is the alignment of the microstrands along the printing direction which contributed to the formation of anisotropic structures and alignment of cells. 313 The mechanism of shear thinning in the nozzle of extrusion printers using entangled inks is illustrated in Figure 21, along with our current understanding of how molecules, nanoparticles, and microgels align and/or deform during flow. In each of these examples, stabilization of the structures by photo-activated materials can be advantageous.…”
Section: Figure 19 Common Strategies To Achieve Good Extrusion Printabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Among these forms, hydrogels are the most applicable and injectable forms of scaffolds in 3D bioprinting owing to their cell‐encapsulating capability and good biocompatibility. [ 95 ] Cells and morphogens can be loaded within the hydrogel solution prior to the gelling via curing agents and through alternations in pH, ionic concentration, and temperature. [ 73 ] As previously discussed, there are two types of hydrogels: natural and synthetic based on their origins.…”
Section: Materials and Biomaterials For 3d‐printable Hydrogels For Bomentioning
confidence: 99%
“…Such hydrogels have been developed in previous studies using either porogen, [ 14,15 ] leachable particles, [ 16 ] nanoclay, [ 17 ] granular particles, [ 18 ] self‐assembly, [ 19,20 ] or polymer degradation. [ 21 ] Bioprintable pore‐forming formulas, such as aqueous two‐phase emulsion system [ 12,22,23 ] and hydrogel microstrands, [ 24 ] could be used for injection as well. These hydrogels, however, suffer from limited pore size and low interconnectivity, which impair permeability and performance.…”
Section: Introductionmentioning
confidence: 99%